Biogas generation potential from anaerobic digestion of “Ponkan” and “Montenegrin” Tangerine peel waste - Carvalho, Rafael Vieira de; Abreu, Thais Cristina Campos de; Romanel, Celso (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Due to the increase in human damage caused to the environment, there is a need for remediation measures and techniques to be applied in favor of a sustainable future for upcoming generations. One of the sectors that have potential in the use of low carbon economy stocks is agribusiness. In fact, part of agribusiness is fruit growing which is one of the sectors of greatest Brazilian economic prominence, with a wide variety of crops produced throughout the country and in different climates. In the food production chain, there are several post-harvest losses and the consequent generation of large amounts of waste. Anaerobic digestion presents itself as an excellent and promising option for the treatment of food waste, contributing to the fight against the increase of polluting emissions and generating biogas for use as thermal or electric energy or even as a fuel to replace fossil fuels. The anaerobic digestion of organic waste is a biological process characterized by the absence of oxygen which through the metabolic activities of microorganisms causes the complex organic material to be converted mainly into methane and carbon dioxide. In a scenario where the production of waste around the world is growing more and more, efficient waste treatment techniques are essential to ensure lower greenhouse gas emissions in the environment. In this study, the biodegradation capacity of the substrate formed with “ponkan” and “montenegrin” tangerine peels was investigated through BMP (Biochemical Methane Potential) tests with the determination of water content, total solids, and volatile solids in samples of laboratory under ideal conditions of pH, temperature, and humidity. The tests were carried out over a period of twenty-one days, having been found, in general, a greater production of gas until the twelfth day of testing, with a gradual reduction until stabilization around the twentieth day. The results obtained in laboratory show that there is a positive potential in the generation of biogas using tangerine peels in relation to the peels of other fruits researched in the literature (orange, banana, among others), with a biogas generation potential of 615.38 NmL/gSV for “ponkan” tangerine peel and 565.84 NmL/gSV for “montenegrin” tangerine peel. Brazil, due to its vast territorial extension and favorable climatic conditions, stands out in the international agricultural market and, therefore, holds great potential in the scenario of energy change. Despite the high potential of waste generated in the country, technologies for recovering organic matter are still incipient and even unknown. The results of this research are yet another contribution to reaffirm and publicize the benefits of treating organic matter via anaerobic digestion, with significant economic, social, and environmental advantages.